2006
DOI: 10.1016/j.febslet.2006.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation regulates turnover of cyclooxygenase‐2

Abstract: Cyclooxygenase-2 (COX-2) catalyzes the rate-limiting step in the prostanoid biosynthesis pathway, converting arachidonic acid into prostaglandin H 2 . COX-2 exists as 72 and 74 kDa glycoforms, the latter resulting from an additional oligosaccharide chain at residue Asn 580 . In this study, Asn 580 was mutated to determine the biological significance of this variable glycosylation. COS-1 cells transfected with the mutant gene were unable to express the 74 kDa glycoform and were found to accumulate more COX-2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…To explain the lack of reduction on PGE 2 production in the presence of mPGES-1 siRNA, the authors speculate that COX-2 might be the rate-limiting enzyme responsible for the production of PGE 2 , as suggested also by others (Degousee et al, 2003;Mancini et al, 2007;Sevigny et al, 2006). More important, the authors also demonstrated that MK-886, a compound reported to decrease mPGES-1 activity, reduces the expression of mPGES-1 but upregulates COX-2 (B˚age et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…To explain the lack of reduction on PGE 2 production in the presence of mPGES-1 siRNA, the authors speculate that COX-2 might be the rate-limiting enzyme responsible for the production of PGE 2 , as suggested also by others (Degousee et al, 2003;Mancini et al, 2007;Sevigny et al, 2006). More important, the authors also demonstrated that MK-886, a compound reported to decrease mPGES-1 activity, reduces the expression of mPGES-1 but upregulates COX-2 (B˚age et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have suggested that Asn-67, Asn-144, and Asn-410 are primarily co-translationally N-glycosylated and that glycosylation of these sites facilitates COX-2 maturation in the ER (37) through a process that probably involves the ER chaperones calnexin and/or calreticulin (38). Asn-594, the fourth N-glycosylation site of COX-2, is variably glycosylated (37,39,40) and does not need to be glycosylated for the enzyme to achieve a catalytically competent conformation (37). Instead, we have found that post-translational N-glycosylation of Asn-594 is important for the degradation of huCOX-2 expressed in HEK293 cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activity of NF-κB can be regulated by O-GlcNAcylation [139], which is known to be upregulated in multiple cancer types [45]. Similarly, the pro-inflammatory molecule COX2 is also regulated by glycosylation [140], and the efficiency of some COX2 inhibitors is thought to be dependent on COX2 glycosylation state [141]. Interestingly, a diet derived sialic acid called N-glycolylneuraminic acid (Neu5Gc, found primarily in red meat) can be incorporated in human tissues.…”
Section: Tumour Promoting Inflammationmentioning
confidence: 99%